TRANSFORMING SOCIAL LIFE IN BALINESE SOCIETY THROUGH PANCASILA VALUES IN THE ERA OF DIGITALIZATION - I Gusti Ngurah Santika; I Wayan Kandia; Heliyarko Koba Natara; Yohanes Nagel (International Conference on Multidisciplinary Research Perspective, 2025)
This study explores the transformation of social life in the communities of Klungkung and Karangasem, Bali, based on the values of Pancasila amidst the rapid digitalization era. Utilizing a qualitative case study approach, data were collected through interviews, focus group discussions, participant observation, and document analysis involving community leaders, youth, elders, digital content creators, and local government officials. The findings reveal that Pancasila remains a fundamental ideological foundation for social cohesion and cultural identity, manifested through traditional rituals and communal practices. At the same time, digital platforms serve as new spaces for expressing and adapting Pancasila values, especially among younger generations. However, intergenerational differences in perspectives and emerging ethical challenges such as misinformation and cyberbullying indicate the need for digital literacy programs grounded in Pancasila principles. This study concludes that sustaining Pancasila values in Bali’s social life requires integrated efforts encompassing cultural preservation, ethical digital adaptation, and multi-generational dialogue to ensure social harmony in the digital era. The results contribute to broader understandings of how national ideology interacts with local culture and technology in contemporary Indonesian society.